A novel synonymous SNP in PITX3 is associated with Parkinson’s disease in a Chinese population (Swiss Medical Weekly, 2012)
BACKGROUND AND PURPOSE: Paired-like homeodomain transcription factor 3 (PITX3) is an important transcription factor for differentiation and survival of dopaminergic neurons. Recent reports have shown a strong association of polymorphisms in the PITX3 gene with Parkinson’s disease (PD). Our study was designed to verify whether three previous PITX3 SNPs (rs2281983, rs4919621 and rs3758549) were associated with PD in the Chinese population. We also investigate the association of novel polymorphisms in PITX3 gene with PD. METHODS: All the polymorphisms of PITX3 we found in this study were sequenced by PCR products from both directions with dye terminator methods using an ABI-3100 sequencer. We included 356 sporadic PD patients and 300 healthy elderly people as controls. RESULTS: We provide evidence for strong association of a novel polymorphism c.219G>A (p = 0.000307) with PD. Our data showed that the substitution of c.219G>A in PITX3 Exon 3 was significantly higher in PD compared with control. Previous finding suggesting three SNPs (rs2281983, rs4919621 and rs3758549) in the PITX3 gene to be associated with PD could not be replicated. CONCLUSIONS: Our findings indicate that a novel synonymous SNP in PITX3 gene may contribute to PD risk in the Chinese population.